Sistem Pakar Untuk Diagnosa Penyakit Demam Berdarah - Danang Tri Wahyujana, Didik Nugroho, Muhammad Hasbi (Jurnal Ilmiah SINUS, 2012)
Artificial intelligence is part of computer science that make for the machine (computer) can do the job as good as yangdilakukan and human. One area of study that is pakar.Sistem good expert system designed to solve a particular problem by mimicking the work of experts. In the health sector, an expert system is developed to perform disease diagnosis. One of the diseases that need the experts that dengue fever. The purpose of design expert system is that users can perform diagnosis of dengue fever based on the symptoms entered into the system. The method used in this knowledge base is the trace method developed. Methods of data collection included interviews and a literature review of both books and discourses on the internet. The results of the consultation with this system shows that the system is able to determine the disease based on symptoms and suggestions entered by the user Keywords: Artificial Intelligence, Expert Systems, tracking forward, Fever bloody